If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 5(-5) = -17 Multiply 5 * -5 8x + -25 = -17 Reorder the terms: -25 + 8x = -17 Solving -25 + 8x = -17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 8x = -17 + 25 Combine like terms: -25 + 25 = 0 0 + 8x = -17 + 25 8x = -17 + 25 Combine like terms: -17 + 25 = 8 8x = 8 Divide each side by '8'. x = 1 Simplifying x = 1
| x66^-2/3 | | -6t=t^2-t^3 | | (3w+5)(8-w)=0 | | y-2+x-3=17 | | 1.5*x=90 | | a+ib=3+3a+3ib+4i+4ia-4b | | -2z+6-10z=-10-8z | | .75x-4=10+.25x | | -3+2=-10y+30 | | 3-(-4)=n | | N=3-(-4) | | x^4-100x^2+4761=0 | | N=3-n | | 24y^10+32y^7= | | 6+6c=-10+2c | | 93=200t | | 4xn=56 | | 6x=-y-11 | | -(-3-4y)-8y=-7 | | -(-3-4)-8y=-7 | | 3x-7=4.8x | | g+10=3g-8 | | 1/2(n-6)=1 | | 7x^2-9x+6= | | 17x+23y=7 | | 1-(-2b/1a) | | x=16-8x | | 8(x+3)=-3(9-4x)+17 | | (a+ib)-2(a-ib)+7-6i=0 | | x=28.8-8x | | .5x+3-4x=.75x-.25 | | -9s-9=-8s |